BIBLIOMETRIC MAPPING OF DISCIPLINARY MANAGEMENT IN PUBLIC AND MILITARY ORGANIZATIONS FROM A SYSTEMIC PERSPECTIVE: CONTRIBUTIONS FOR THE INTERNAL AFFAIRS DIVISION OF THE CBMSC - Basílio, Rodrigo Gonçalves; Basílio, Nicole Zanon; Demarchi, Murilo Pedro; Pertile, Laura (Seven Editora, 2025)
This article analyzes how disciplinary management in public and military organizations has been discussed in the scientific literature, using the experience of the Internal Affairs Office of the Military Fire Brigade of Santa Catarina (CBMSC) as a reference. The research adopts General Systems Theory as its conceptual basis, considering that institutional discipline results from the interaction of integrated and dynamic subsystems. To this end, it develops a bibliometric analysis with a quantitative and descriptive approach, using the Web of Science, SciELO, and Scopus databases between June and July 2025. The searches were structured in English, Portuguese, and Spanish, with keywords combined using Boolean operators. The results indicate that the scientific production on disciplinary management remains fragmented, with emphasis on isolated authors and poorly articulated collaborative networks. There is a concentration of studies in English-speaking countries, while in SciELO the approach is punctual and normative. It is concluded that there are still important gaps, highlighting the need for further research to assess the applicability of the references found in order to improve processes, decision-making tools, and innovation practices within CBMSC, especially in its internal affairs context, thus strengthening governance, ethics, and transparency in the public service.DOI: https://doi.org/10.56238/sevened2025.029-076